Balzac et les géographes : reconversion d’un discours scientifique - Huaulmé, Killian (Studia Romanica Posnaniensia, 2023)
The paper is an attempt at showing how the mentions and quotations of contemporary geographic discourses inserted in the Balzacian texts and paratexts are there to outline the features of a new novelistic æsthetic. We will start from the following observation: the Balzacian novel and its encyclopedic ambition are contemporaneous with the first attempts of some geographers to found a unified science from a diversified set of knowledges and practices. Therefore, modern geography may appear as an adversary of Balzac’s own ambition of totalization and we will show that geographic discourse, rather than being a model for him as other scientific discourses are, is distorted in his novels, deprived of its epistemological value and reduced to a science without knowledge.